1981
DOI: 10.1042/cs0600055
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Radioisotope Methods for the Measurement of Phosphate Absorption in Normal Subjects and in Patients with Chronic Renal Failure

Abstract: 1. Intestinal phosphate absorption was measured in normal subjects, in patients with chronic renal failure, and in post-transplant patients, by a double isotope technique involving oral administration of 32P and simultaneous intravenous injection of 33P with subsequent deconvolution analysis. 2. By this technique intestinal phosphate absorption has been shown to have two components: an initial rapid phase, which is completed by 3 h, and a slower more prolonged phase, which continues beyond 7 1/2 h. 3. Phosphat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

1983
1983
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 16 publications
2
19
0
Order By: Relevance
“…Net absorption of phosphorus (absorption/secretion from pancreatic and biliary fluids) is roughly 65% but may vary depending on the bioavailability of the phosphorus source, 25-hydroxyvitamin D [25(OH)D], and the relative amounts of phosphorus and calcium (69, 8587, 139, 162). The entire intestinal tract absorbs phosphorus, although most of the absorption occurs in the small intestine (47, 66, 101, 132, 133). The two main pathways for intestinal phosphate absorption are a passive paracellular pathway and an active type II sodium-dependent phosphate transporter ( Npt2b ) in the intestine, which have been studied in mice and rats (70, 114).…”
Section: Phosphorus Metabolism In Healthmentioning
confidence: 99%
“…Net absorption of phosphorus (absorption/secretion from pancreatic and biliary fluids) is roughly 65% but may vary depending on the bioavailability of the phosphorus source, 25-hydroxyvitamin D [25(OH)D], and the relative amounts of phosphorus and calcium (69, 8587, 139, 162). The entire intestinal tract absorbs phosphorus, although most of the absorption occurs in the small intestine (47, 66, 101, 132, 133). The two main pathways for intestinal phosphate absorption are a passive paracellular pathway and an active type II sodium-dependent phosphate transporter ( Npt2b ) in the intestine, which have been studied in mice and rats (70, 114).…”
Section: Phosphorus Metabolism In Healthmentioning
confidence: 99%
“…However, literature on this topic is mixed. In humans, reduced phosphorus absorption has been demonstrated in patients with end-stage kidney disease in older metabolic balance studies as well as radioisotope phosphorus tracers, (11)(12)(13) and in patients on hemodialysis by a triple-lumen perfusion technique. (14) These findings have been supported in some but not all studies in experimental rat models: Peerce and colleagues (15) showed decreased sodium-dependent jejunal brush border membrane vesicle (BBMV) phosphorus uptake in 5/6 nephrectomized rats (ie, subtotal nephrectomy) versus age-matched controls, and we (16) previously found a reduction in active phosphorus transport by Ussing chamber in Cy/+ CKD rats at 21 weeks of age compared to normal rats, though this effect appeared to be driven by the groups of rats treated with phosphate binders.…”
Section: Introductionmentioning
confidence: 99%
“…From the recent com parison of the various methods of Ca absorp tion by using radioactive Ca, the double iso tope Ca absorption test has emerged as the method of choice for detail investigation of the Ca absorption mechanism, but the single tracer method has proven to give reasonable and sufficient estimates of absorption rates such to be useful for clinical purposes [20,21], Even for the study of Pi intestinal ab sorption in man, a variety of techniques have been proposed involving the administration of radioactive Pi either as a single or double isotope. Also in this case the comparison of the various methods has led to the conclusion that the more simple and reliable test for clin ical purposes is the single-tracer method, based on studies of plasma radioactivity after the oral administration of radioactive Pi [ 22], Ca absorption and Pi absorption can be simultaneously estimated following a com bined oral dose of 45Ca and 32P in a carrier of 20 mg Ca (as Ca chloride) and 50 mg Pi (as disodium hydrogen phosphate) according to the method of Peacock et al [23] based on plasma sampling during 4 h after tracer ad ministration. The activity of each single iso tope may be distinguished by liquid scintilla tion counting of samples, since beta-emis sions of 32P and 45Ca differ substantially in energy content.…”
Section: Hormones and The Intestinal Absorption Of Calcium And Phosphmentioning
confidence: 99%